Accessibility in times of remote teaching (Research, Society and Development, 2021)
Digital accessibility is a mechanism for reaching any and all content on the web in which all people must have the help of others, regardless of their need. The virtual resources incorporate aspects that involve understanding, interaction and navigation. Since the turn of the century, in the early 2000s, we have heard that we are living in the digital age. Almost 21 years later, we find ourselves increasingly immersed in technology, now more than ever enhanced by social isolation. In this sense, the teaching-learning process has become increasingly challenging. Based on these issues, we aim to analyze the legal aspects that address accessibility, considering the context of remote education experienced from the Digital Technologies of Information and Communication. Thus, due to the nature of the objectives established in this work, we understand that the research is of a qualitative approach, and of a methodological, exploratory and bibliographic nature. The results show that all this pandemic situation in which we find ourselves is complex and challenging and that several difficulties are also present in the school scenario and that the need for teachers and students to reinvent themselves is undeniable. Furthermore, it challenges management teams, teachers, students and families. With regard to remote education, one aspect to be considered is a digital exclusion especially of the portion of the population that has some disability, as digital technology can also reach people with disabilities, while there are applications, software and equipment that enable accessibility to information, entertainment, sociability and other benefits. Anyway, schools must problematize and rethink a way of using and learning technology can and must be an ally of teaching-learning and be able to provide several benefits. Thus, the expectation is that its use will become common.